TEACHING WRITING NEWS ITEM BY USING BROADCAST NEWS VIDEO TO SENIOR HIGH SCHOOL STUDENTS - Dwi Ewilsa Noviane; Witri Oktavia (Universitas Negeri Padang, 2018)
Based on the writer’s experience, many students have difficulties in writing news item text, such as they lack of idea to write; the way of delivering ideas and vocabulary; inappropriate strategy or media when doing teaching and learning process. In order to solve these problems, an appropriate teaching technique is needed to help students improve their ability in writing news item text. This paper is aimed at explaining how to use broadcast news video in teaching writing news item text. Broadcast news video is conducted by showing the students broadcast news video with subtitle which in color. After that, the teacher asks the students to write the phrase that they watch from the video. Then the students discuss with their friends. Next, the students with the teacher help arrange their phrase into a short news item text. Finally, the students present their writing as a news anchor randomly in front of the class. The objective of this paper is to help the students and to improve students’ ability in writing news item text.